2018
DOI: 10.3233/jad-180137
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid and Muscarinic Signaling Crosstalk in the 3xTg-AD Mouse Model of Alzheimer’s Disease

Abstract: The endocannabinoid system, which modulates emotional learning and memory through CB1 receptors, has been found to be deregulated in Alzheimer's disease (AD). AD is characterized by a progressive decline in memory associated with selective impairment of cholinergic neurotransmission. The functional interplay of endocannabinoid and muscarinic signaling was analyzed in seven-month-old 3xTg-AD mice following the evaluation of learning and memory of an aversive stimulus. Neurochemical correlates were simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 67 publications
2
25
1
Order By: Relevance
“…HU 210 ameliorated the memory deficits of olfactory bulbectomized (OBX) rats [ 114 ]. In contrast with what was previously reported, chronic treatment with WIN 55,212-2 significantly normalizes this cognitive deficit in old Tg APP mice accompanied by a reduction in the inflammation and an increased Aβ clearance [ 115 , 116 ]. Chronic administration of the selective CB1 agonist ACEA at pre-symptomatic or early AD stages reduced the learning and memory deficits observed in the double APP/PS1 transgenic mice.…”
Section: Cannabinoids and Endocannabinoid Systemscontrasting
confidence: 79%
“…HU 210 ameliorated the memory deficits of olfactory bulbectomized (OBX) rats [ 114 ]. In contrast with what was previously reported, chronic treatment with WIN 55,212-2 significantly normalizes this cognitive deficit in old Tg APP mice accompanied by a reduction in the inflammation and an increased Aβ clearance [ 115 , 116 ]. Chronic administration of the selective CB1 agonist ACEA at pre-symptomatic or early AD stages reduced the learning and memory deficits observed in the double APP/PS1 transgenic mice.…”
Section: Cannabinoids and Endocannabinoid Systemscontrasting
confidence: 79%
“…Previous reports have demonstrated that sub-chronic administration of JZL184, an irreversible inhibitor of the MAGL, promotes downregulation and G-protein uncoupling of CB1R (22,23). We found that administration of JZL184 (8 mg/kg, i.p.)…”
Section: Jzl184 Administration Corrects Behavioral Impairment In CD Micementioning
confidence: 67%
“…The reported compensation would affect receptors coupled to other types of G proteins, however, as previously mentioned, we were only able to analyze those coupled to the G i/o subtype. It is improbable that CB 1 receptors play a role since previous results reported a similar distribution regarding the CB 1 receptor autoradiographic densities compared to functional autoradiography stimulated by specific agonists such as the WIN55212-2 (Llorente-Ovejero et al, 2018). However, it has not been yet possible to get the distribution of LPA 1 receptors.…”
Section: Discussionmentioning
confidence: 97%